Reformar el artículo 42 de la ley orgánica de servicio público, para garantizar el principio de imparcialidad en el juzgamiento de las faltas administrativas a las y los servidores públicos - Gaona Vaca, Fricson George (2016)
The public servant to serve in Public Administration may be subject to a number of disciplinary offenses which may well be due to start administrative proceedings. It ie by the actions or omissions of the servants or public servants who violate the provisions of law in force in the Republic and this law, as it pertains to rights and constitutional or statutory prohibitions, which are sanctioned by the appointing authority or his delegate. That is who has the authority to sanction a disciplinary offense, which incurred a servant or a public servant, whether they are serious or minor offenses, it is the appointing authority or his delegate to the same public institution where the fault is caused, which in many cases either affection or disaffection, it is punishable server violating the principle of impartiality laid down in Art. 75 of the Constitution of the Republic of Ecuador, which states that everyone has the right to free access to justice and effective, impartial and expeditious protection of their rights and interests, subject to the principles of immediacy and speed, in any case will be defenseless, and therefore the start of unfair and arbitrary summaries that violate the principle of impartiality. I can see that the appointing authorities as the provision already cited the Organic Law of the Public Service punish sometimes affection, disaffection or political affinity of some form blatantly run counter to the principles set out in Art says. 1 LOSEP such as equality and non-discrimination. Le the sanction is applied according to the affinity, friendship and cronyism, the highest authority with the sumariado server, which I think should be tried and punished for "Internal Control Agency, composed of the Head of the Administrative Unit talent of the entity; A representative of the Ministry of Labour Relations; and counsel for the institution" where if necessary step to the legal institution of the administrative proceedings, to ensure the principle of impartiality, established in the Constitution.